Algal turf sediments across the Great Barrier Reef: Putting coastal reefs in perspective. (December 2018) - Tebbett, Sterling B.; Goatley, Christopher H.R.; Bellwood, David R.
Abstract: Sediments trapped within algal turfs play a key role in mediating ecosystem processes on reefs. Despite this ecological importance, our understanding of turf-bound sediments on coastal reefs is limited, even though such reefs are heavily exposed to terrestrial sediments. We compared algal turf sediment loads, composition and grain size distributions among coastal reefs along the Great Barrier Reef (GBR) and compared these to turf-bound sediments on reefs across the GBR. Algal turf sediment loads on coastal reefs were on average 9.4 times higher than offshore reefs (range 2.2–16.1 times). Among coastal reefs there was marked variability in the loads (797.87–3681.78 g m −2 ), composition (organics 1.0–8.9%; silicates 27.4–93.0%) and grain size of sediments. Our data highlight the potential variability in physical and ecological factors that control sediment dynamics on coastal reefs, including proximity to rivers, and reveal that turfs on coastal reefs are heavily influenced by sediments. Highlights: Sediments in algal turfs were examined on coastal reefs of the Great Barrier Reef. Algal turf sediments were also compared among coastal and offshore reefs. Algal turf sediment loads and composition varied among coastal reefs. Coastal algal turf sediment loads were up to 16-fold higher than offshore reefs. Sediments are likely to influence processes associated with turfs on coastal reefs.